The chain mediating role of rumination and psychological resilience in symptom burden and kinesiophobia in patients with chronic heart failure - Li, Mengqi; Cheng, Lina; Jiang, Yu (Frontiers in Psychiatry, 2024)
ObjectiveTo explore the chain-mediating role and impact of rumination and psychological resilience on symptom burden and kinesiophobia in patients with chronic heart failure.MethodsWe selected a total of 318 patients with chronic heart failure from a hospital in Wuxi between November 2023 and May 2024 using a convenience sampling method. Various scales and questionnaires assessed general information, symptom burden, resilience, rumination thinking, and kinesiophobia. Statistical analysis was conducted using SPSS and the bootstrap method to examine the chain mediation effect.ResultsThe scores for symptom burden, rumination, psychological resilience, and kinesiophobia in patients with chronic heart failure were 0.81± 0.47, 50.63± 9.02, 23.43± 6.26, and 38.91± 8.01, respectively. Mediation analysis showed that symptom burden had a direct positive predictive effect on rumination (β = 0.475, 95% CI: 0.365–0.584), rumination had a direct negative predictive effect on psychological resilience (β = -0.199, 95% CI: -0.306–0.092), and psychological resilience had a direct negative predictive effect on kinesiophobia (β = -0.273, 95% CI: -0.340–0.206). Rumination and psychological resilience played a chain mediation role between symptom burden and kinesiophobia, with a total effect of 0.606, a direct effect of 0.380, and an indirect effect of 0.226. The mediation effect accounted for 37.29% of the total effect.ConclusionKinesiophobia is at a high level in patients with chronic heart failure. Symptom burden can affect patients’ kinesiophobia through the independent or chain mediation effects of rumination and psychological resilience. Healthcare professionals should actively adopt strategies to address symptom burden and rumination while enhancing psychological resilience to reduce patients’ kinesiophobia.